Semiotika Michael Riffaterre: Analisis Pembacaan Heuristik-Hermeneutik atas Puisi Ughniyatul Fushul al-Arbaah Karya Sulaiman al-Issa - Wati, Wiwit Rahma; Mustofa, Ady Muh. Zainul (Fakultas Keguruan dan Ilmu Pendidikan,Universitas Jambi, 2023)
This study aims to search for the meaning of Ughniyatul Fushul al-Arbaah poetry by Sulaiman al-Issa, who is well known as the king of children poets. The descriptive qualitative method is used in this study. The theory used in this study is Michael Riffaterres semiotics. To get the meaning in poetry, Riffaterre suggested two stages of reading, namely heuristic and hermeneutic reading. Heuristic reading focuses on lexical meaning, while hermeneutic reading is not only based on lexical but also comprehensively on the supporting aspects of the literary work. The result of heuristic reading of Ughniyatul Fushul al-Arbaah poetry revealed that the poetry generally described nature and seasons. While hermeneutic reading revealed that seasons symbolize the phase of life. They consist of happiness and sadness. The writer motivated the children to not lose hope and consider that the phase of life makes life more worthy.